STRATEGI PENGEMBANGAN DAN PENINGKATAN USAHA JAMU HERBAL TRADISIONAL (STUDI PADA WARUNG IBU PEBRI JL. PULAU OBI GANG DURIAN SINGARAJA) - SUDARNAYA, I KETUT; ASRI, DESAK MADE TIARA (Universitas Mahasaraswati K. Mataram, 2023)
The purpose in this study is to know. Strategy for Development and Improvement of Traditional Herbal Medicine Business (Study at Warung Ibu Pebri Jl. Obi Island Gang Durian Singaraja) The type of research used is a type of qualitative descriptive research. The data collection techniques used are interview techniques and documentation techniques. As for The results in this case can be seen from 2 aspects, namely: 1. For Warung Bu Ferbi, a) product quality, b) product prices, c) technology benefits, d) customer satisfaction, 2. For consumers, a) there is an improvement in product quality, b) product price adjustments, c) the use of technology in product marketing, d) there is satisfaction felt by customers with the products sold.